Geosite assessment and management proposals of Cape Mondego Natural Monument (Western Portugal) - Rocha, João Nuno Correia (2011)
The remarkable geodiversity of the Jurassic outcrops justifies the implementation of strategies in order to conserve and promote the geosites of Cape Mondego. This protected area was created aiming the promotion of the geological heritage conservation, scientific research and environmental education. The Cape Mondego Natural Monument is well-known worldwide due to its international stratigraphical relevance given by the ocurrence of two stratotypes: the Global Boundary Stratotype Section and Point (GSSP) for base of the Bajocian Stage and the Auxiliary Section and Point (ASSP) for the base of the Bathonian Stage. A management plan was developed for this protected area.